Factors Affecting the Business Success of Vietnamese Entrepreneurs in Luang Prabang Province - Trinh Huy Tiep, bounthavy (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aimed to examine the business operations of Vietnamese entrepreneurs in Luang Prabang, and to identify the key factors influencing their business success. A quantitative research method was employed, using a structured survey to collect both primary and secondary data from a sample of 167 Vietnamese entrepreneurs operating in Luang Prabang. Data were analyzed using basic descriptive statistics frequency, percentage, mean, and count—via SPSS for Windows (Version 25). The findings revealed that the majority of respondents were male (50.3%), married (70.1%), and primarily engaged in service-based businesses (41.3%). Most businesses were fully foreign-funded (47.9%), and 27.5% had been operating for 3–6 years. A large portion of entrepreneurs (22.8%) reported a monthly income between 51–100 million LAK. In terms of internal factors, respondents identified management as the most critical, followed by marketing, and the use of machinery and tools, with an overall mean score of 3.51, indicating a high level of importance. Key internal success factors were effective management practices and skilled personnel. Further analysis revealed five external factors with a statistically significant positive impact on business success (p < 0.05): production materials (X₄), financial factors (X₅), economic conditions (X₇), cultural and social factors (X₉), and technology (X₁₀). Other examined factors were not statistically significant at the 0.05 level.